Mining off the map: fulongchang and silver mines in the Qing Empire’s far Southwest - Kim, Nanny; Yang, Yuda (Journal of the economic and social history of the Orient, 2021)
Abstract A donation stele discovered in the 1980 records that the community of the Fulong silver mines raised some 4500 liang of silver to build a temple dedicated to the God of Wealth in 1814. The site in a remote mountain range in northern Yunnan evidently was a prosperous and populous mining town. Yet it appears in no government record. Centered on the case study, this paper provides insights into social self-organization of communities and the structures within the Qing government that allowed the operation of mines that were registered with the local governments and submitted taxes yet kept out of the communications with the central government. The analysis contributes a specific example of communal governance structures and explains the two layers in late imperial administration, one which was official and documented in gazetteers and central records, and another which was customary and usually undocumented.
Gesehen am 15.02.2022